Introduction to Proteomics : Tools for the New Biology - Liebler, Daniel C (Humana Press, 2002)
Advances in genome sequencing, analytical instrumentation, and computing power have excitingly transformed the practice of biology by now making it possible to understand complex biological systems as collections of proteins-proteomes. In Introduction to Proteomics: Tools for the New Biology, Daniel C. Liebler masterfully introduces the science of proteomics by spelling out the basics of how one analyzes proteins and proteomes, and just how these approaches are then employed to investigate their roles in living systems. He explains the key concepts of proteomics, how the analytical instrumentation works, what data mining and other software tools do, and how these tools can be integrated to study proteomes. Also discussed are how protein and peptide separation techniques are applied in proteomics, how mass spectrometry is used to identify proteins, and how data analysis software enables protein identification and the mapping of modifications. In addition, there are proteomic approaches for analyzing differential protein expression, characterizing proteomic diversity, and dissecting protein-protein interactions and networks. Comprehensive, concise, and easy-to-read, Introduction to Proteomics: Tools for the New Biology provides researchers new to proteomics with all the essential concepts and background needed to use the powerful new proteomic techniques in their research, to make intelligent requests to proteomics service facilities, and to better understand and utilize the rapidly growing proteomics literature.